Psychological/behavioral interventions for emerging adults with chronic pain - Foy, Judith G.; Kechichian, Sandra; Foy, Michael R.; Ziadni, Maisa (Frontiers in Pain Research, 2024)
Emerging adults, of whom significant numbers report chronic pain, are characterized as having unique needs and challenges. Psychological/behavioral treatments found to be beneficial for reducing pain outcomes in children and adults are understudied in emerging adults. Following a systematic review of the literature, our objective is to report on quantitative studies of psychological/behavioral interventions for chronic pain in emerging adults.We conducted a search of six databases (Cochrane Central Register of Controlled Trials, Google